Evidence for internuclear signaling in drosophila embryogenesis. Issue 8 (2nd July 2015) - Buckalew, Richard; Finley, Kara; Tanda, Soichi; Young, Todd
<x xml:space="preserve">Abstract</x> Background : Syncytial nuclei in Drosophila embryos undergo their first 13 divisions nearly synchronously. In the last several cell cycles, these division events travel across the anterior–posterior axis of the syncytial blastoderm in a wave. The phenomenon is well documented but the underlying mechanisms are not yet understood. Results: We study timing and positional data obtained from in vivo imaging of Drosophila embryos. We determine the statistical properties of the distribution of division times within and across generations with the null hypothesis that timing of division events is an independent random variable for each nucleus. We also compare timing data with a model of Drosophila cell cycle regulation that does not include internuclear signaling, and to a universal model of phase‐dependent signaling to determine the probable form of internuclear signaling in the syncytial embryo. Conclusions: The statistical variance of division times is lower than one would expect from uncoordinated activity. In fact, the variance decreases between the 10th and 11th divisions, which demonstrates a contribution of internuclear signaling to the observed synchrony and division waves. Our comparison with a coupled oscillator model leads us to conclude that internuclear signaling must be of Response/Signaling type with a positive impulse. Developmental Dynamics 244:1014–1021, 2015. © 2015 Wiley Periodicals, Inc.